OPTIMIZATION ASSIGNMENT OF WESTERN PATROL UNIT (KRI) ELEMENT IN SEA SECURITY OPERATIONS IN RIAU ISLANDS WATER AREAS USING SET COVERING MODEL - Agus Setiadji; Didit Herdiawan; Benny Sukandari; Muksin Muksin (JOURNAL ASRO, 2020)
The territorial waters of Riau Islands are one of the locations with a high level of vulnerability to violations in thesea in Indonesia, because this region is directly adjacent to neighboring countries and is an international tradeand shipping route. One of the roles of the Indonesian Navy is to maintain the security of national jurisdictions,including in the territorial waters of Riau Islands, which are then realized in Operation Sea Security, where theimplementation still has several constraints, namely budget constraints, technical capabilities, number of ships,limited information, and limitations supporting facilities, so that the implementation of Marine SecurityOperations is not optimal. The main reason is the placement of patrol boats during operations is not wellorganized. With these problems, a study was conducted using the set covering method to get the most optimallocation for patrol boat placement with as few ships as possible but still be able to reach the entire waters of theRiau Islands and minimize operational costs. In this study a discrete approach was taken, namely thedetermination of the critical points, which numbered 37 vulnerable points. All these points must be affordable bythe ship on duty.Keywords: Set Covering, Location Selection, Marine Security Operations, Riau Islands Waters Region